1998
DOI: 10.1099/00221287-144-11-3149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analysis of pTAV320, a repABC-type replicon of the Paracoccus versutus composite plasmid pTAV1

Abstract: The second replicator region of the native plasmid pTAVl of Paracoccus versutus has been identified thus proving the composite nature of this replicon. The minimal replicon designated pTAV320 (43 kb) was cloned and sequenced. pTAV320 encodes three putative proteins -RepA, RepB and RepC.This replicator region shows strong structural and functional similarity t o mpABC-type rep1 icons found in several Agrobacterium and Rhizobium plasmids. The origin of replication appears to be localized within the coding sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 28 publications
2
62
0
1
Order By: Relevance
“…The E. coli-specific mobilizable vector pABW1 (Bartosik et al, 1997) was digested with PstI and ligated with the 2?9 kb entrapment cartridge from pGBG1 (Schneider et al, 2000). The resulting plasmid (pMMB1) was digested with XbaI and KpnI and ligated with a 5?6 kb linear form of the repABC-containing mini-replicon pTAV320 (Bartosik et al, 1998), recovered from shuttle plasmid pABW22A (Table 1). The resulting positive selection vector was designated pMMB2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E. coli-specific mobilizable vector pABW1 (Bartosik et al, 1997) was digested with PstI and ligated with the 2?9 kb entrapment cartridge from pGBG1 (Schneider et al, 2000). The resulting plasmid (pMMB1) was digested with XbaI and KpnI and ligated with a 5?6 kb linear form of the repABC-containing mini-replicon pTAV320 (Bartosik et al, 1998), recovered from shuttle plasmid pABW22A (Table 1). The resulting positive selection vector was designated pMMB2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1; see Methods for details). This plasmid was a fusion of: (i) an E. coli-specific vector, pABW1 (Bartosik et al, 1997); (ii) mini-replicon pTAV320, carrying a repABC-type replicon originating from low-copy-number plasmid pTAV1 (107 kb) of Paracoccus versutus UW1 (Bartosik et al, 1998); and (iii) a cI-tetA selective cartridge (Schneider et al, 2000).…”
Section: Identification Of Tnppa1mentioning
confidence: 99%
“…Two different-sized replicons were obtained: (i) pMSA5 -containing a 3.5-kb EcoRI restriction fragment of pSinA, and (ii) pMSA10 -containing a 4.5-kb BamHI restriction fragment of pSinA. Sequencing showed that pMSA10 carries: (i) a single replication initiation protein gene (repC) (ORF3) without other components of the typical repABC operon (Bartosik et al, 1998), (ii) a gene potentially involved in recombinational resolution of plasmid multimers (mrs; ORF4) and (iii) two additional genes: phd (ORF5) and pemK (ORF6), which probably create a putative hybrid phd-pemK addiction system. Despite the absence of the repAB genes, pMSA10 was still able to replicate in various representatives of Alphaproteobacteria, including: A. tumefaciens LBA288, Brevundimonas sp.…”
Section: Plasmid Psina Is Responsible For Arsenite Oxidationmentioning
confidence: 99%
“…The size of particular RepA proteins and their N-terminal DNA binding domain suggest that the segregation systems of most rhizobial repABC replicons are Type Ia and thus are members of the MinD/ParA superfamily [14,23]. RepA and RepB proteins in conjunction with parS, a centromere-like sequence, provide the plasmid segregation machinery, which is required for efficient maintenance of the lowcopy DNA replicons in a dividing population of rhizobial cells [18,20,24]. The third protein-encoding gene of the operon, repC, is essential for plasmid replication ( Figure 1).…”
Section: Rhizobial Plasmid Maintenance Systemsmentioning
confidence: 99%
“…The third protein-encoding gene of the operon, repC, is essential for plasmid replication ( Figure 1). RepC, an initiator protein, functions by binding to the origin of replication oriV located within its own coding sequence, close to or inside of a large A+T region [18,24,25]. The repC gene is the minimal region sufficient for replication when inserted into a non-replicating (e.g.…”
Section: Rhizobial Plasmid Maintenance Systemsmentioning
confidence: 99%